Role of TNF alpha and IL-6 in Inflammatory Process after Tooth Extract in Children Under 12 Years (Indian Journal of Forensic Medicine & Toxicology, 2020)
A cross-sectional study was carried out in Kirkuk city from of November 2018 to March 2019. The number of children after tooth extraction under study were 55 children ages were between 5-12 years old. These patients admitted to private clinics of dentists. The control group who were matched to the children with tooth extraction studied, included 35 healthy children. Three ml of blood was collected by vein puncture using Vacutainer tubes from each patient enrolled in this study for determination the level of IL-6 and TNF-? by using ELISA technique. The study showed that the highest mean level of TNF-? was found in children after tooth extraction comparing with healthy control group( 36.8±13.4 v.s. 13.5 ±2.9 pg/ml) (P: ?0.05). The highest mean level of IL-6 was found in children after tooth extraction comparing with control (88.1±15.7 v.s. 21.7±7.13 pg/ml) (P: ?0.05). The study showed that the highest mean level of TNF-? was found in children after tooth extraction in the first week of after tooth extraction (33.2±9.1 pg/ml) and the level was still decreased to be the lowest level after one month tooth extraction of children (20.18±2.9 pg/ml), the result was significant (P: ?0.05). The study showed that the highest mean level of IL-6 was found in children in the first week of after tooth extraction (92.1±15.8 pg/ml) and the level was still decreased to be the lowest level was after one month of tooth extraction (67.9±9.81 pg/ml), the result was significant (P: ?0.05).